IMPLEMENTATION OF THE SIMPLEX METHOD IN MAXIMIZED DONUT PRODUCTION PROFITS AT ARSYILA BAKERY - Gayus Simarmata; Juli Antasari Br Sinaga; Lilis; Yuliana Nainggolan; Jelli Sijabat; Vania Yocelin Sagala (RADJA PUBLIKA, 2024)
Arsyila Bakery, a bakery MSME, faces challenges in determining the most efficient donut production combination. Production decisions have been based on intuition, potentially leading to waste of raw materials and inability to generate maximum profits. This study aims to formulate a Linear Program model as a decision-making tool in determining donut production strategies, namely Potato Donuts x_1 and Milk Donuts x_2, in order to obtain optimal daily profits. A quantitative approach is used through the Linear Program optimization method with the objective function of maximizing profits z = 3000x_1 + 2000x_2, which is limited by nine constraints of raw material availability and production capacity. The model is solved using the Simplex Method algorithm through POM-QM software for Windows. The analysis results show that the optimal solution is achieved by producing 8 units of Potato Donuts and 0 units of Milk Donuts, resulting in a maximum profit of Rp24,000 per day. The binding constraints in the model are Sugar and Potatoes, which are the main limiting factors of production. The economic value (shadow price) indicates that the addition of sugar has the greatest impact on increasing profits, at IDR 2,000 per kilogram, followed by potatoes at IDR 5,000 per kilogram. Based on these findings, it is recommended that Arsyila Bakery implement this optimal production combination and prioritize increasing sugar stock to support improved operational performance and achieve higher profits.